Friends or foes: can we make a distinction between beneficial and harmful strains of the Stenotrophomonas maltophilia complex? - Berg, Gabriele; Martinez, Jose L. (Frontiers in Microbiology, 2015)
Stenotrophomonas maltophilia is an emerging multi-drug-resistant global opportunistic pathogen of environmental, mainly plant-associated origin. It is also used as a biocontrol or stress protecting agent for crops in sustainable agricultural as well as in bioremediation strategies. In order to establish effective protocols to distinguish harmless from harmful strains, our discussion must take into consideration the current data available surrounding the ecology, evolution and pathogenicity of the species complex. The mutation rate was identified as one of several possible criteria for strain plasticity, but it is currently impossible to distinguish beneficial from harmful S. maltophilia strains. This may compromise the possibility of the release and application for environmental biotechnology of this bacterial species. The close relative S. rhizophila, which can be clearly differentiated from S. maltophilia, provides a harmless alternative for biotechnological applications without human health risks. This is mainly because it is unable to growth at the human body temperature, 37∘C due to the absence of heat shock genes and a potentially temperature-regulated suicide mechanism.